Identifying modifiable factors related to novice adolescent driver fault in motor vehicle collisions. (18th August 2021) - Pitt, Tona M.; Howard, Andrew; HubkaRao, Tate; Hagel, Brent
Abstract: Objective: Novice adolescent drivers have a higher propensity to engage in risky driving and are at higher odds of being involved in collisions. Graduated driver licensing programs have been instituted to help novice drivers gain experience while avoiding higher risk driving circumstances. This study examines modifiable risk factors contributing to novice adolescent driver fault in collisions. Methods: Police traffic collision report data from municipalities in Alberta for the years 2010–2016, inclusive, were used. Fault in collision was assigned using an automated and previously validated tool for assigning culpability. Factors contributing to novice adolescent (16-19 years of age) fault in collision were examined using multivariable logistic regression. Results: Novice adolescent drivers had higher adjusted odds ratios (aOR) of being at-fault in collision when driving from 01:00-05:00 (aOR = 1.38; 95% Confidence Interval [CI]: 1.26-1.50). Novice adolescent drivers had lower odds of fault when driving with an adult (aOR= 0.62; 95% CI: 0.57-0.68) or a single peer (aOR= 0.87; 95% CI: 0.80-0.94), but higher odds of causing a severe collision with a single peer present (aOR= 2.23; 95% CI: 1.21-4.11). Impairment of the teen driver was reported in 25% of all fatal collisions, and 40% of late-night fatal collisions. Conclusions: The findings support policies that allow driving with a single adult or peer passenger during daytime hours. Driving during late-night hours should be restricted for novice adolescent drivers.